PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH DAN KOMPETENSI APARATUR PEMERINTAH DESA TERHADAP PENCEGAHAN FRAUD DALAM PENGELOLAAN DANA DESA DENGAN AKUNTABILITAS SEBAGAI VARIABEL INTERVENING - Oktavie Fresiliasari (ITB AAS INDONESIA, 2023)
This study aims to determine the effect of the government's internal control system variables and the competency of village government officials on fraud prevention with accountability as an intervening variable. This research is a survey research. Questionnaires were distributed to respondents using a mail survey. The research object was the Village Government in Aimas District, Sorong Regency, with a research population of 231 respondents, with a total sample of 120. Respondents' answers were processed as many as 108. The sample used purposive sampling method. The collected data were analyzed using the Partial Least Square (PLS) method with the WarpPLS software version 7.0. The results of the study show that the government's internal control system has a significant positive effect on accountability and fraud prevention. While competence has no effect on accountability, competence has a significant positive effect on fraud prevention. The results of the mediation test confirmed that accountability is an intervening variable related to the effect of the government's internal control system on fraud prevention, whereas accountability is not an intervening variable related to the influence of competence on fraud prevention.